2021
DOI: 10.2337/dc20-2049
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Polyexposure, Polygenic, and Clinical Risk Scores in Risk Prediction of Type 2 Diabetes

Abstract: OBJECTIVE To establish a polyexposure score (PXS) for type 2 diabetes (T2D) incorporating 12 nongenetic exposures and examine whether a PXS and/or a polygenic risk score (PGS) improves diabetes prediction beyond traditional clinical risk factors. RESEARCH DESIGN AND METHODS We identified 356,621 unrelated individuals from the UK Biobank of White British ancestry with no prior diagnosis of T2D and normal HbA 1c levels. Using self-reported and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 46 publications
(44 reference statements)
5
45
0
Order By: Relevance
“…As known exposures impacting PSD are still limited and no major advances in the field have been observed recently, agnostic exposure-wide analytical approaches that take into account of inter-correlation may provide further understanding of other, so far, unknown factors that also cover other domains of the exposome such as internal (e.g., inflammation) and external (e.g., chemical, lifestyle, psycho-social) correlates (13). In this regard, similar to previous studies in other phenotypes such as HIV (46), diabetes (47), depression (48), and childhood behavior (49), our research group is currently conducting a systematic exposomewide investigation of correlates of psychosis expression in the UK Biobank.…”
Section: Future Directionssupporting
confidence: 65%
“…As known exposures impacting PSD are still limited and no major advances in the field have been observed recently, agnostic exposure-wide analytical approaches that take into account of inter-correlation may provide further understanding of other, so far, unknown factors that also cover other domains of the exposome such as internal (e.g., inflammation) and external (e.g., chemical, lifestyle, psycho-social) correlates (13). In this regard, similar to previous studies in other phenotypes such as HIV (46), diabetes (47), depression (48), and childhood behavior (49), our research group is currently conducting a systematic exposomewide investigation of correlates of psychosis expression in the UK Biobank.…”
Section: Future Directionssupporting
confidence: 65%
“…Our study adds to knowledge on the interplay between genetic and lifestyle factors by formally investigating whether polygenic scores for type 2 diabetes capturing overall genetic risk or distinct pathophysiological mechanisms could help prioritize individuals who would benefit the most from targeted dietary recommendations. Previous studies have shown no appreciable interactions between genetic and lifestyle factors on the development of type 2 diabetes [ 6 , 9 , 31 ], indicating that genetic risk does not modify the beneficial effect of healthy lifestyle interventions. However, previous studies considered a limited number of variants to generate type 2 diabetes polygenic scores, and the lack of significant interactions reported in these studies is often attributed to the mixture of variants affecting different pathways into a single score [ 6 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies investigating the incremental value of PRSs integrated to clinical risk scores, CHD PRSs have yielded varying performance improvements over routinely used clinical risk assessment tools, such as PCE or QRISK3 4 , 16 18 . For T2D, the improvements with PRS over clinical risk assessment tools have been moderate 4 , 19 . Here, when added on top of with age and sex, the PRS CHD had a higher AUC for incident CHD than any of the eight other individual risk factors of GRIT-CHD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the primary care data allowed us to calculate the QRISK3 and QDiabetes clinical scores more accurately as they were derived using the same data sources 28 , 29 . Following the recommendations in recently published reporting guidelines for genetic prediction studies 30 , and in contrast to previous studies 5 , 16 19 , we used the external UK Biobank cohort for out-of-sample evaluation of our risk tools. As the predictive performance of risk models can greatly worsen when assessed outside of their derivation datasets 31 , our results indicate that GRIT-CHD and GRIT-T2D may generalize well also to other cohorts.…”
Section: Discussionmentioning
confidence: 99%